PENGARUH KUALITAS PELAYANAN, PROMOSI, DAN BRAND AWARENESS TERHADAP MINAT NASABAH MENABUNG PADA PRODUK SIMPEDES BANK BRI - Mia Angelina; Syafrizal Chan (Universitas Mercu Buana, 2022)
This study aims to examine and analyze the effect of service quality, promotion and brand awareness on saving interest on Rakyat Indonesia Bank (Study on Kantor Cabang Pembantu Batusari, Jakarta Barat) The data of this research are data taken from the company's secondary data and primary data obtained from the processing of questionnaire data filled out by out by prospective consumers with an interest in saving money on Simpedes Product. The number of samples used as many as 100 respondents and the analysis technique used in this study is to use Partial Least Square (PLS) analysis. Based on the results of data analysis in this study, it shows that the service quality variable has a positive and significant effect, the promotion variable shows positive but not significant results, and the Brand Awareness variable shows positive and significant results on customer interest in saving.